Pemanfaatan Mendoan Sebagai Media Pembelajaran Tematik Berbasis HOTS pada Materi Pemanfaatan Sumber Daya Alam untuk Kelas IV Madrasah Ibtidaiyah di Kabupaten Banyumas - Aji, Untung Setyo (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
This research was motivated by the lower ability of students to think at a higher level (Heigh Order Thinking Skill). One of the offers was by utilizing an interesting learning media, which uses mendoan as a learning mediaum to improve higher order thinking skills. This research aims to examine the effectiveness of the use of mendoan as a thematic learning media based on HOTS on the use of natural resources in everyday life. The method used was qualitative research with action research. This research was conducted in MI Muhammadiyah Beji in class IV with 14 students. Analysis techniques using triangulation techniques, namely collecting data, reducing data, then display data research. Based on the results of the analysis, it was known that there was ana increases in the ability of heigh order thinking skill students in understanding the material utilization of natural resources in everyday life. This was based on the classification of higher order thinking skill processes, namely: knowing, appliying, analiyzing, evaluating, an creating. The results of this research, students who scored above the KKM as many 93% of a total 14 students based on learning output using media mendoan.